What's Right With Men? Gender Role Socialization and Men's Positive Functioning. Issue 1 (February 2019) - Cole, Brian P.; Baglieri, Michael; Ploharz, Scott; Brennan, Margaret; Ternes, Michael; Patterson, Tristan; Kuznia, Ashley
This study explored relations between conformity to masculine norms, gender role conflict, hope, and psychological well-being among a sample of 389 men from a university, with a predominantly White student body, located in the Midwestern United States. Bivariate correlations revealed that men's conformity to masculine norms and gender role conflict were positively correlated. Bivariate correlations revealed no significant relations between conformity to masculine norms, trait hope, and psychological well-being. Gender role conflict was associated with decreased hope and psychological well-being. Results of path analysis explained relations between conformity to masculine norms, gender role conflict, trait hope, and psychological well-being. This indicates that gender role conflict may contribute to lower trait hope and psychological well-being for college men. Although several aspects of conformity to masculine norms had positive associations with hope, these relations were significant and negative when men experienced gender role conflict. This work fills an important gap in the literature by examining the unique relations of conformity to masculine norms and gender role conflict to men's positive functioning. Results are discussed within the context of positive psychological theories including Frederickson's broaden and build theory of positive emotions, hope theory, Ryff's model of psychological well-being, and self-determination theory. Implications and future directions are discussed.